DESIGN OF ACCOUNTING INFORMATION SYSTEM AND FINANCIAL REPORTING IN COVINDO LIVING - Santi Yopie; Felicia Aw (ConCEPt - Conference on Community Engagement Project, 2022)
The purpose of this practical work is the availability of an accurate accounting record system, capable of presenting transaction records in Covindo Living's business reports. Covindo Living's operational recording still uses book-based records that contain a list of customers, types of goods, prices, and sales amounts based on the date of the transaction. This accounting recording system specially designed according to Covindo Living's needs and hopes that the system can be used sustainably to run daily operations. The output of this research is Microsoft Office Access which automatically generates financial reports, including statements of financial position, profit or loss, purchase report, sales report, and inventory report. The data collection methods used are survey, interview, and observation. The implementation of work at Covindo Living goes through the stages of preparation, implementation, and research as well as reporting with a period of four months, starting from September until December 2021. After implementation, Covindo Living's financial transactions are recorded completely and neat, financial reports are accurate so that owners can make the right decisions according to business conditions.